Development of a Web-Based E-Module for Food and Beverage Preparation Course for Vocational Students in Upper Secondary (PVMA) - NURUL NABILA BINTI RAZMAN; Yasak, Zurina (Research and Innovation in Technical and Vocational Education and Training, 2024)
Designing and creating an online e-module for the Food and Beverage Preparation Course (FBPC) specifically for Upper Secondary Vocational Students (PVMA) is the objective of this study. To improve theoretical knowledge and practical skills, the e-module integrates interactive multimedia, simulations, and assessments. Learning material developers provided an online e-module for the Food and Beverage Preparation course. Designing and developing the e-module and testing its usability and functionality are the study's objectives. The ADDIE Model provides the foundation for the design and development process. A clear and understanding teaching flow could be developed with the aid of storyboards, flow charts, and hierarchical charts. This e-module was developed using the Google Site platform. Canva was employed by the study to generate graphic and multimedia content for the e-module. Wordwall is frequently used in educational activities. To assess the product's functionality, 14 experts were given the checklist form. Results for interaction design are 100% agreeable, while interface design is 92.9% agreeable, and content design is 92.9% agreeable. After that, 38 students performed the pretest and posttest. With a value of t = -3.118 and sig = 0.004 (p < 0.05) between the pre-test and the post-test, there is a significant difference in the use of the e-module before and after. In summary, the PVMA teaching and learning process can make use of this e-module